Impact of Professional Development Program on Student Achievement in Ghana - Offei Kwakye, Dennis (Yayasan Lembaga Studi Makwa, 2023)
Continuous professional development (CPD) is critical for college tutors to maintain their effectiveness as educators and keep their teaching practices up-to-date. By investing time and effort in CPD, tutors can provide a better learning experience for their students and ensure that they are well-equipped to meet the challenges of a rapidly changing educational landscape. In this regard, the study examined how the CPD impacted the student’s Satisfaction, Academic Achievement, and Classroom Engagement. The study further assessed the moderating role of the tutor’s teaching strategies and the student’s learning strategies. A quantitative study and a quasi-experimental design were used to demonstrate links between the study variables. A sample of 346 students was taken from a total population of 3200 students, and a sample of 191 teachers was taken from a population of 380 teachers using Krejcie and Morgan (1970). The data was coded with SPSS version 23 and transferred to SmartPLS4 for a partial least square regression analysis. The study found that the teacher’s continuous capacity development was the important factor influencing students’ academic performance. Besides, their teaching and the student’s learning strategies. For policy recommendations in resources allocation to improve student’s academic achievement, management should first focus on assisting teachers with better classroom management, and career development and improve their teaching skills through the CPD programs. Abstrak Pengembangan profesional berkelanjutan (CPD) sangat penting bagi pengajar perguruan tinggi untuk mempertahankan efektivitas mereka sebagai pendidik dan menjaga praktik pengajaran mereka tetap mutakhir. Dengan menginvestasikan waktu dan tenaga dalam CPD, tutor dapat memberikan pengalaman belajar yang lebih baik bagi siswanya dan memastikan bahwa mereka diperlengkapi dengan baik untuk menghadapi tantangan lanskap pendidikan yang berubah dengan cepat. Dalam hal ini, penelitian ini mengkaji bagaimana CPD berdampak pada Kepuasan siswa, Prestasi Akademik, dan Keterlibatan Kelas. Penelitian ini lebih lanjut menilai peran moderasi dari strategi pengajaran tutor dan strategi pembelajaran siswa. Penelitian kuantitatif dan desain eksperimen semu digunakan untuk menunjukkan hubungan antar variabel penelitian. Sampel diambil sebanyak 346 siswa dari total populasi 3200 siswa, dan sampel guru diambil sebanyak 191 siswa dari populasi 380 guru dengan menggunakan Krejcie dan Morgan (1970). Data diberi kode dengan SPSS versi 23 dan ditransfer ke SmartPLS4 untuk analisis regresi kuadrat terkecil parsial. Studi ini menemukan bahwa pengembangan kapasitas guru yang berkelanjutan merupakan faktor penting yang mempengaruhi kinerja akademik siswa. Selain itu, pengajaran mereka dan strategi belajar siswa. Untuk rekomendasi kebijakan dalam alokasi sumber daya untuk meningkatkan prestasi akademik siswa, manajemen pertama-tama harus fokus pada membantu guru dalam pengelolaan kelas yang lebih baik, dan pengembangan karir serta meningkatkan keterampilan mengajar mereka melalui program CPD.